The performance of a herd of N'dama cattle in the forest zone of Ghana - Serekye, A.Y. (1986)
Herd performance of N'Dama at Baodi farm from 1971 to 1985 is evaluated. Reproduction records of N'Dama were analysed. Year of birth significantly affected age at first calving and calving interval, while month of birth did not have significant effect on age at first calving and calving interval. The results showed high performance of N'Dama herd in the humid zone. Improvement of reproductive performance could be achieved through culling of females with long calving intervals and replacing them with heifers selected from high producing cows.